IMPROVEMENT OF FEEDING PRACTICES FOR STUNTING CHILDREN UNDER TWO YEARS THROUGH AN COMPLEMENTARY FEEDING EDUCATION - Erna Julianti; Elni; Restu Amalia Azmy (Nurse and Health, 2023)
Background: Feeding practice is one of the factors determining the stunting prevalence. It happens because the children’s food intake strongly depends on the feeding practice done by their parents. The role of parents would determine children's nutritional intake, in which inappropriate nutritional intake lead to stunting.